Comparison of Harmonic Scalpel and Electrocautery During Breast Surgery: A Cohort Study - Hassan Moaiery; Mohammad Yahya Faridi (Gazi Medical Journal)
Objective: As one of the most frequent procedures, breast surgery incurs high healthcare costs. The significance of surgical quality and complications before and after breast surgery entailed the use of methods with the highest outcomes and the least complications. Methods: Throughout this research, postoperative complications and factors affecting the quality of surgery were evaluated in the Kowsar Hospital between 2019 and 2020 for patients requiring breast surgery. Patients undergoing breast surgery were randomly categorized into two groups: electrocautery (A) and harmonic scalpel (B). Results: Of the 56 patients, 28 were in group A, and the remaining 28 were in group B. Intraoperative bleeding, drainage rate, period of drainage, and duration of hospitalization in group B were significantly lower (p<0.05). Furthermore, the extent of pain in both groups was different (p<0.001), so that there was less postoperative pain in women who experienced harmonic breast surgery. Patients throughout group A reported more complications than in group B, such that 7 (25%) patients underwent limb anesthesia and 3 (10.7%) patients experienced seroma, suggesting a higher risk of complications in group A; however, the difference between the two groups was not significant in terms of limb anesthesia (p=0.069) and serum (p=0.075). Conclusion: Harmonic scalpel usage in breast surgery has fewer complications, better operation quality, and shorter hospital stay than other older methods; therefore, the use of harmonic scalpels may substitute for different surgical strategies.